Current state of the problem of assessing the quality of life in patients with cervical cancer after organ-preserving treatment - O. S. Dil; A. L. Chernyshova; L. N. Balatskaya; Yu. M. Truschuk; A. A. Chernyakov (ABV-press, 2024)
An indicator of the effectiveness of treatment of cancer patients, in addition to oncological results, is also the preservation of their quality of life. Quality of life assessment is a modern research method that allows identifying even minor changes in any spheres of human activity in order to comprehensively determine the effectiveness of treatment. The quality of life of cancer patients is a priority and promising area of modern medicine.The article presents information about the current state of the problem of quality of life of patients with cervical cancer after organ-preserving treatment. The results of a number of foreign studies published on this topic are presented. In addition, the results of a prospective study conducted in the Department of Gynecology of the Tomsk Oncology Research Institute are presented. In conclusion, the need for additional study of reproductive results and determining which factors need to be further evaluated, speaking of a comprehensive assessment, is shown.